Foucault e as teorias do reconhecimento interfaces com a filosofia da educação - Almeida, Jonas Rangel (Editora Oficina Universitária, 2021)
Text analytics runs through three theoretical fields [...] of recognition. Taylor, Honneth and Butler [...] approached to bring out the hypothesis that such theories are not enough to reach a utopian body, that is, a different political mobility as a result of the updates demanded in the contemporary world. It is here that Foucault's thought erupts. [...] what is delineated, affirmed and desired in the text are other bodies for recognition in frank development. [...] what is on stage is a genealogy of a long Erfindung, that is, of a long invention of Recognition, with a capital R. Such an invention, in turn, interposes itself between the fleeting flight of Minerva in the penumbra that insists on announcing itself and the dawns that remain to happen - Nietzsche, remembering Rigveda, said: "There are so many dawns that have not yet shone". What possible dawns for another policy of recognition? What arises, from there, for the art of government, education and lives? Since Western Bildung, perhaps too tired for not recognizing itself, asks: where, how and why would the inclusion of unrecognized bodies be limited there? [...] How many containers for the philosophy of education are there? And for thought? And for subjectivity? And for neoliberalism? And for the conscience that recognizes? And for the typified face that typifies the alien face? And for the body that will be abjected? And for the morbid gesture of the repetition of bureaucratic jouissance? And for so many strangers and excluded from this society?